Mitotic Activity in Glioblastoma Correlates with Estimated Extravascular Extracellular Space Derived from Dynamic Contrast-Enhanced MR Imaging - Mills, S.J.; du Plessis, D.; Pal, P.; Thompson, G.; Buonacorrsi, G.; Soh, C.; Parker, G.J.M.; Jackson, A. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: A number of parameters derived from dynamic contrast-enhanced MR imaging and separate histologic features have been identified as potential prognosticators in high-grade glioma. This study evaluated the relationships between dynamic contrast-enhanced MRI–derived parameters and histologic features in glioblastoma multiforme.MATERIALS AND METHODS: Twenty-eight patients with newly presenting glioblastoma multiforme underwent preoperative imaging (conventional imaging and T1 dynamic contrast-enhanced MRI). Parametric maps of the initial area under the contrast agent concentration curve, contrast transfer coefficient, estimate of volume of the extravascular extracellular space, and estimate of blood plasma volume were generated, and the enhancing fraction was calculated. Surgical specimens were used to assess subtype and were graded (World Health Organization classification system) and were assessed for necrosis, cell density, cellular atypia, mitotic activity, and overall vascularity scores. Quantitative assessment of endothelial surface area, vascular surface area, and a vascular profile count were made by using CD34 immunostaining. The relationships between MR imaging parameters and histopathologic features were examined.RESULTS: High values of contrast transfer coefficient were associated with the presence of frank necrosis (P = .005). High values of the estimate of volume of the extravascular extracellular space were associated with a fibrillary histologic pattern (P < .01) and with increased mitotic activity (P < .05). No relationship was found between mitotic activity and histologic pattern, suggesting that the correlation between the estimate of volume of the extravascular extracellular space and mitotic activity was independent of the histologic pattern.CONCLUSIONS: A correlation between the estimate of volume of the extravascular extracellular space and mitotic activity is reported. Further work is warranted to establish how dynamic contrast-enhanced MRI parameters relate to more quantitative histologic measurements, including markers of proliferation and measures of vascular endothelial growth factor expression.DCE-MRIdynamic contrast-enhanced MRIEnFenhancing fractionGBMglioblastoma multiformeIAUC60initial area under the contrast agent concentration curveKtranscontrast transfer coefficientvevolume of the extravascular extracellular space per unit tissue volumeVEGFvascular endothelial growth factorvpvolume of the blood plasma per unit tissue volume